Customer Satisfaction And Product Quality As Intervening Variables - Arief Syah Safrianto (International Journal of Economics and Management Research, 2023)
The purpose of this study project is to clarify two things: (1) how product quality affects customer happiness among Xiboba beverage product customers in Jakarta; and (2) how price affects customer satisfaction among Xiboba beverage product consumers in Jakarta. (3) How product quality affects product consumers' loyalty to a product. Drinks Xiboba in Jakarta (4) Price's Impact on Customer Loyalty Among Jakartan Xiboba Drink Product Users Customers in Jakarta who purchased Xiboba Drink Products. This study employs a quantitative methodology and an associative type. The participants in this study are those who buy Xiboba drinks in the Jakarta region. In the meantime, the sample consists of 92 respondents who are over the age of 18 and reside in Jakarta and purchase and consume Xiboba beverage products on a regular basis. Path analysis techniques are employed for data analysis. The results of the analysis of this research activity showed that Price (X2) and Product Quality (X1) both had positive and significant effects on Customer Satisfaction (Z), Customer Loyalty (Y) and Product Quality (X1) had a positive and significant effect on Customer Loyalty (Z).